2010
DOI: 10.1097/hjh.0b013e328332c36b
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension incidence in Turkey (HinT): a population-based study

Abstract: Follow-up periods scheduled considering age, initial blood pressure category, and body mass index are important for the early determination of hypertension. As there are limited data regarding hypertension incidence in developing countries, the results of data collected in this study might serve as a model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 17 publications
6
42
0
10
Order By: Relevance
“…In the Whitehall II trial in the UK, testing validation of FHRPS, the predicted hypertension risk was similar to the observed incidence of hypertension (18). A similar situation was found in our study, in which the predicted hypertension risk was similar to the observed incidence of hypertension in the HinT study (10).…”
Section: Results Expressed As No (%) CI = Confidence Intervalsupporting
confidence: 89%
See 1 more Smart Citation
“…In the Whitehall II trial in the UK, testing validation of FHRPS, the predicted hypertension risk was similar to the observed incidence of hypertension (18). A similar situation was found in our study, in which the predicted hypertension risk was similar to the observed incidence of hypertension in the HinT study (10).…”
Section: Results Expressed As No (%) CI = Confidence Intervalsupporting
confidence: 89%
“…Blood pressure is only controlled in 28.7% of patients with hypertension in Turkey (6), compared with 29.6% of men and 34% of women in developing countries, and 33.2% of men and 38.4% of women in developed countries (5). According to the Turkish incidence of hypertension (HinT) study, the 4-year incidence of hypertension was 21.3% (10).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings generally confirm those of other studies where hypertension prevalence was associated with lower education, unmarried, obesity, diabetes and family history of CVD. 27,31,32 Our findings importantly document low awareness of hypertension among those with elevated BP. In our study, only 38.8% reported having been told by a health care provider that they had high BP.…”
Section: Discussionmentioning
confidence: 54%
“…Salt intake, obesity and sedentary lifestyle are common among hypertensive patients as well as in general population. 14,31,33 Second, patients may not take medications out of fear of drug interactions, perceived lack of effectiveness, adverse effects, misunderstanding regarding necessity, the absence of symptoms associated with hypertension or concerns about costs. 34 Patients who report better general communication with their doctor, better instructions on how to take a medication and who receive more medication information are more likely to take medications as prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypertension were recruited from three population-based field studies (Hypertension Incidence in Turkey study, 11 Salt Intake and Blood Pressure in Turkey study, 12 and one unpublished study) conducted by the Turkish Society of Hypertension and Renal Diseases. All of the above-mentioned studies used a two-stage stratified sampling method to select a nationally representative sample of the adult population over 18 years of age.…”
Section: Study Design and Participantsmentioning
confidence: 99%